The portrayal in the Spanish press of migration caused by climate change: a moral framework analysis - Prieto-Andrés, Antonio; Fernández-Romero, Cayetano; Aguareles, Marina (Frontiers in Communication, 2025)
This study analyzes how migrations due to climate change and environmental causes are represented in the leading Spanish newspapers, but from a novel perspective, linking variables such as the topics that are covered the most or the most commonly used news sources to the typology of moral frames applied. This typology is based on the moral responsibility of the media when it comes to representing climate or environmental migrants. The methodology of quantitative content analysis, combined with framing theory, was used. The findings indicate that the Spanish press presents this issue from the perspective of the intellectual elite, seeking to analyze the phenomenon with rigor, relying on experts, and combining the coldness of the data with a good dose of empathy toward the migrants’ situation. With regard to the most common topics, the causes of this type of migration stand out, along with the legal issues affecting migrants. The predominant portrayal is of the migrant as a victim, but also as a political subject, with their portrayal as a threat remaining very limited, which is novel when compared with other studies, in which this aspect holds greater relevance. In terms of moral frameworks, the one in which migrants are viewed as a biological life is most prevalent (32.1%), followed by that of empathy (30%) and hospitality (25%), with the one that views migrants as a threat having largely fallen by the wayside (11.4%). This paper also analyzes the combinations of this framework with the mentioned variables to identify possible correlations.